Certificate of conformity as a tool for regulating urbanization and preserving its urban tissue - MOKADEM, Racha; KHENOUSSI, Karima (Journal of Human Sciences, 2020)
This article aims to present the certificate of conformity as one of the effective legal tools in the field of urban planning, highlighting its role of regulation and control in the construction process through the inquiry conducted by the commission the conformity of the completed works with the approved plans and the building permit, The building, its dimensions, its use and its facade, as well as the planned development works.The purpose of this study is to clarify the function of the Certificate of Conformity as a license to use the building and its operation according to the purpose for which it was built, showing its status as a basic document allowing the owner to possess his establishment and to reveal the right of the rejected applicant to an administrative appeal before the competent administrative authorities, and appeal to the competent courts if necessary.The provisions of Executive Decree No. 19/15 of 25 January 2015 on the preparation and the procedures of urban planning acts will be the main source for the study of this theme, as well as other relevant legal texts.